2023
DOI: 10.1007/s13593-023-00869-w
|View full text |Cite
|
Sign up to set email alerts
|

Modeling adaptation of sorghum in Ethiopia with APSIM—opportunities with G×E×M

Abstract: Sorghum is an important food and feed crop in the dry lowland areas of Ethiopia. Farmers grow both early-sown long-duration landraces and late-sown short-duration improved varieties. Because timing and intensity of drought stress can vary in space and time, an understanding of major traits (G), environments (E), management (M), and their interactions (G×E×M) is needed to optimize grain and forage yield given the limited available resources. Crop simulation modeling can provide insights into these complex G×E×M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Among the wheat across different locally grown early, medium, and late-growing cultivars such as Hartog [ 18 ], HAR-2501 (Hawi) [ 19 ], Hawi, and Digelu cultivars [ 20 ] were used for APSIM wheat calibration and validation. For sorghum model calibration and validation, locally available cultivars Gigrite [ 21 ], Meko, and Jigurti [ 22 ] were used. Since maize is the most modeled crop in Ethiopia using the APSIM system, lots of locally grown cultivars are tested in different years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the wheat across different locally grown early, medium, and late-growing cultivars such as Hartog [ 18 ], HAR-2501 (Hawi) [ 19 ], Hawi, and Digelu cultivars [ 20 ] were used for APSIM wheat calibration and validation. For sorghum model calibration and validation, locally available cultivars Gigrite [ 21 ], Meko, and Jigurti [ 22 ] were used. Since maize is the most modeled crop in Ethiopia using the APSIM system, lots of locally grown cultivars are tested in different years.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the above-presented results in Table 1 , other additional specific study places were identified from Ref. [ 22 ] research such as Humera (Western Tigray), Axum (Central Tigray), Shiraro (North-Western Tigray), Debark (North Gonder), Shoa Robit (North Shewa), Kobo (North Wollo), Sirinka (North Wollo), Jijiga (Fafan), Babile (Eastern Hararge), Metehara (East Shewa), Konso (Konso), Gato (Konso), and Kayafer (South Omo) by growing the crops in Melkassa and Miesso. Among the different researchers, Chemura et al [ 26 ] try to predict the yield of maize in large study areas including Assosa, Guraghe, Hadiya, Illubabor, Jimma, Kemashi, Metekel, North Gonder, North Shewa, North Wollo, Sidama, South Gonder, West Gojam, and West Tigray.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The APSIM model is well suited to investigate GxExM factors influencing cropping systems performance (Holzworth et al, 2014;Rotili et al, 2020;Winn et al, 2022;Tirfessa et al, 2023). The crop models within APSIM simulate grain yield and other aspects such as biomass production and partitioning, root growth, water use, and N uptake as a function of weather conditions and environmental stresses .…”
Section: Description Of the Study Locations And Apsim Modelmentioning
confidence: 99%